Pakistan’s Water Security Crisis: Challenges and the Case for Integrated Water Resource Management - Safia Mansoor (NUST Journal of International Peace and Stability)
Water security has emerged as the greatest security concern for Pakistan. Despite being endowed with abundant water resources, the country is steadily heading towards a severe water crisis due to excessive exploitation and widespread mismanagement. In the past, issues pertaining to water security were largely neglected, paving the way for its transformation into an existential threat with alarming consequences for Pakistan. The combination of inadequate water availability, deteriorating water quality, rising demand, and the compounded pressures of climate change and population growth underscores the severity of this crisis. This research examines Pakistan’s critical water security challenges and explores potential future risks. The study is grounded in the theoretical framework of ‘water security’, and the methodology used is the STEEPLE Analysis to foreground multifarious key factors behind burgeoning water insecurity in Pakistan. It argues that Pakistan’s water crisis stems from a complex interplay of interconnected social, political, and economic factors, each with far-reaching implications. To address this crisis, the research advocates for the urgent and effective implementation of an Integrated Water Resources Management (IWRM) approach.